Structure and Variability of the Calls of Polypedates Leucomystax (Amphibia: Rhacophoridae) From Negros, Philippines - Brzoska, Josef; Joermann, Gerhard; Alcala, Angel C. (Silliman Journal, 2024)
Polypedates 1. -leucomystax Boie on the island of Negros calls daily during the rainy season, beginning at twilight. Three calls -can be distinguished. Typical mating calls have an average duration of 190 ms and are composed of 16 pulses. Short calls differ from these not only in being more brief but also in having fewer pulses and a lower frequency range. The third call is characterized by a considerably lower pulse repetition rate. - These data are compared with published descriptions of the calls of P. leucomystax in two other habitats. The mating calls of the Philippine population resemble those of a population in northern Borneo despite significant differences in certain call parameters, but exhibit considerable discrepancies from those of a population in Thailand.